Employee Workload Analysis at Front Office Department of Bunaken Oasis Dive Resort and SPA - Kowel, Hanna Trifena; Lumare, Mercy A.; Sinolungan, Linda (Indo Consultan Energi, 2025)
Employees or workers have an important role in supporting the success of a company or organization. The presence of employees can help the company's operations so that organizational goals can be achieved. This study aimed to analyze the Employee Workload in the Front Office Department of Bunaken Oasis Dive Resort & Spa. This study uses a qualitative method with a descriptive approach. Data collection was carried out through observation and open questionnaires. In order to obtain more objective analysis results, this study uses the formula from the Decree of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis, namely the task-by-task approach method so that the analysis results obtained show that the Employee Workload is relatively high. The subjects of this study were the Front Office Department Employees of Bunaken Oasis Dive Resort & Spa, totaling five employees and 1 Daily Worker. The results of this study indicate that the Workload received by employees is relatively high, in addition to the Workload in the form of physical and mental. As for the factors that influence Employee Workload, from the questionnaire results, several employees stated that the work environment can affect the Workload. Then some employees stated that co-workers and lack of workforce can also affect the Workload, which can hurt employees' physical and mental condition. Therefore, it is necessary to pay attention to the condition and ability of the workforce so that it can have a good impact on the company and the employees.